2004
DOI: 10.1002/ana.20185
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer agents are potent neurotoxins in vitro and in vivo

Abstract: Neurotoxicity of anticancer agents complicates treatment of children with cancer. We investigated neurotoxic effects of common cytotoxic drugs in neuronal cultures and in the developing rat brain. When neurons were exposed to cisplatin (5-100 microM), cyclophosphamide (5-100 microM), methotrexate (5-100 microM), vinblastin (0.1-1 microM), or thiotepa (5-100 microM), a concentration-dependent neurotoxic effect was observed. Neurotoxicity was potentiated by nontoxic glutamate concentrations. The N-methyl-D-aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 57 publications
1
81
0
2
Order By: Relevance
“…A similar reduction was seen in the number of mitotic cells. Other experimental studies suggest that exposure to numerous cytotoxic agents, including cyclophosphamide, cisplatin, ifosfamide, and thiotepa, is associated with significant and dose-dependent neurotoxicity, evident in the cortex, basal ganglia, and hippocampus in 7-day-old animals [95]. These studies, however, did not provide a lineage-based analysis of the toxic effects of chemotherapy.…”
Section: Cell-biological Basis Of Chemotherapy-induced Neurotoxicitymentioning
confidence: 96%
“…A similar reduction was seen in the number of mitotic cells. Other experimental studies suggest that exposure to numerous cytotoxic agents, including cyclophosphamide, cisplatin, ifosfamide, and thiotepa, is associated with significant and dose-dependent neurotoxicity, evident in the cortex, basal ganglia, and hippocampus in 7-day-old animals [95]. These studies, however, did not provide a lineage-based analysis of the toxic effects of chemotherapy.…”
Section: Cell-biological Basis Of Chemotherapy-induced Neurotoxicitymentioning
confidence: 96%
“…In addition, they reported that systemically administration of cisplatin increased the cell death and decreased cell division in the dentate gyrus of the hippocampus and in the corpus callosum. Another study conducted by Rzeski et al 27 reported that cisplatin was the second most neurotoxic anti-cancer drug after vinblastin with 30% neuronal death at 100 µM and 100% neuronal death at 500 . In addition, many previous studies have reported that both short and long term administration of cisplatin causes significant oxidative damage, formation of reactive oxygen species or free radicals in many tissues such as brain, testis, liver, and kidney 24,30 .…”
Section: Comprehensive Neurologic and Neurophysiologic Examinationsmentioning
confidence: 99%
“…Many previous studies have focused on the neurotoxicity of cisplatin in peripheral neuropathy and effectiveness of chemo protective agents 6,18,25,26 . Only a few studies have focused on central neurotoxicity of cisplatin 13,27,28 .…”
Section: Comprehensive Neurologic and Neurophysiologic Examinationsmentioning
confidence: 99%
“…It also markedly interferes with transmethylation reactions, which are crucial for the formation of proteins, lipids and also myelin, presumably leading to demyelination [Harila-Saari et al 1998] of nervous tissues. Cytotoxic agents including methotrexate are potent neurotoxins, which are reported to cause widespread cortical, subcortical, hippocampal and white matter pathologies [Rzeski et al 2004]. Although psychiatric side effects are rare with methotrexate [Levenson, 2006], cognitive and psychiatric disturbances, but not mania, have been reported with methotrexate [Copeland et al 1996].…”
Section: Discussionmentioning
confidence: 99%